2005
DOI: 10.1002/uog.1868
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of the sonographic assessment of fetal sucking and swallowing movements

Abstract: Objective To test the repeatability of sonography in the assessment of fetal sucking and swallowing movements. (−1.4; 1.6), 0.1 (−2.2; 2.3) and −0.6 (−9.0; 7.9), and the mean (95% limits of agreement) intraobserver difference was 0.4 (−3.1; 3.9), 0.1 (−2.0; 2.2) and 1.0 (−10.7; 12.7) for swallowing movements, sucking bursts and total sucking movements, respectively. Methods ConclusionsThe high degree of intra-and interobserver repeatability disclosed in the sonographic analysis of fetal sucking and swallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Unlike that study which was based on experimental manipulation, the current observational result is based on longitudinal modeling techniques. Nonetheless, because amniotic fluid levels are regulated by fetal swallowing and micturition (Einspieler et al, 2012; Levy et al, 2005; Ross & Nijland, 1998), which are more common in active states, these findings suggest that more active fetuses are more active producers of amniotic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike that study which was based on experimental manipulation, the current observational result is based on longitudinal modeling techniques. Nonetheless, because amniotic fluid levels are regulated by fetal swallowing and micturition (Einspieler et al, 2012; Levy et al, 2005; Ross & Nijland, 1998), which are more common in active states, these findings suggest that more active fetuses are more active producers of amniotic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported real-time sonography as a reliable method for the evaluation of fetal movement, particularly fetal facial expressions, in the second and third trimesters. [26][27][28][29][30] These studies reported mouth opening in the context of swallowing, suckling, chewing, and even yawning 28 detected by real-time sonography in fetuses without abnormalities. According to these studies, continued observation by realtime sonography (for anywhere between 15 minutes and 2 hours, depending on the study) is a reliable and reproducible method for visualizing fetal mouth opening.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time fetal breathing movements, which cause fluid flow in the upper respiratory and digestive tracts and observed already in the 1 st trimester suggest that there has been proper growth and maturation of both the lower and upper tracts and their connections with the amniotic fluid cavity. Coordination of these reflexes appears and develops in intrauterine life and depends on appropriate development of anatomical structures of the respiratory and digestive tract structures as well as the nervous system [17]. It may account for more frequent episodes of regurgitation and irregularity of nasal fluid flow spectrum in younger fetuses, as the neural control mechanisms have not yet fully developed.…”
Section: Discussionmentioning
confidence: 99%